﻿Study of the effect of acetylsalicylic acid and a selective arginase II inhibitor KUD 975 on the correction of hemostatic disorders in experimental preeclampsia - Anastasia V. Gureeva; Olga V. Severinova; Vladimir V. Gureev; Indira S. Kochkarova; Elena V. Avdeyeva (Belgorod National Research University, 2022)
Introduction: The disruption of the functional state of the vascular endothelium is among the main causes of preeclampsia, which is one of the most common causes of maternal and perinatal mortality. It can be enhanced by the humoral factors secreted by the activated platelets. The use of acetylsalicylic acid is an effective way to prevent preeclampsia. However, its ability to activate eNOS is a prerequisite for researching its ability to correct the disorders in developing preeclampsia, including by reducing the platelet activity. In this case its effect can be enhanced through increasing the bioavailability of L-arginine by using a selective arginase II inhibitor KUD 975. These facts were the prerequisite for conducting this study. Materials and methods: The study was conducted on 180 female Wistar rats weighing 250-300 g. Acetylsalicylic acid was used at a dose of 7 mg/kg/day and 10 mg/kg/day, KUD 975 - at a dose of 1 mg/kg/day and 3 mg/kg/day. Adenosine diphosphate (ADP, 6.5 microns), arachidonic acid (ASPI, 0.5 mM), and collagen (3.2 mcg/ml) were used as aggregation inducers. Results and discussion: ADMA-like preeclampsia simulation led to an increase in platelet aggregation ability when using all aggregation inducers. This is evidenced by an increase in a degree, rate of aggregation, and a shortened time of thrombus formation. The use of acetylsalicylic acid and a selective arginase II inhibitor KUD 975 led to a decrease in the aggregation ability of platelets and an increase in thrombosis time, while the combined administration of the studied agents showed a more pronounced effect. Conclusion: The data obtained while performing a series of experiments strongly indicate a promising outlook for using acetylsalicylic acid and a selective arginase II inhibitor KUD 975 in order to correct emerging disorders in preeclampsia.